Α-Enolase plays a catalytically independent role in doxorubicin-induced cardiomyocyte apoptosis and mitochondrial dysfunction. (February 2015) - Gao, Si; Li, Hong; Feng, Xiao-jun; Li, Min; Liu, Zhi-ping; Cai, Yi; Lu, Jing; Huang, Xiao-yang; Wang, Jiao-jiao; Li, Qin; Chen, Shao-rui; Ye, Jian-tao; et al.
Abstract: Background: α-Enolase is a glycolytic enzyme with "second jobs" beyond its catalytic activity. However, its possible contribution to cardiac dysfunction remains to be determined. The present study aimed to investigate the role of α-enolase in doxorubicin (Dox)-induced cardiomyopathy as well as the underlying mechanisms. Experimental approaches: The expression of α-enolase was detected in rat hearts and primary cultured rat cardiomyocytes with or without Dox administration. An adenovirus carrying short-hairpin interfering RNA targeting α-enolase was constructed and transduced specifically into the heart by intramyocardial injection. Heart function, cell apoptosis and mitochondrial function were measured following Dox administration. In addition, by using gain- and loss-of-function approaches to regulate α-enolase expression in primary cultured rat cardiomyocytes, we investigated the role of endogenous, wide type and catalytically inactive mutant α-enolase in cardiomyocyte apoptosis and ATP generation. Furthermore, the involvement of α-enolase in AMPK phosphorylation was also studied. Key results: The mRNA and protein expression of cardiac α-enolase was significantly upregulated by Dox. Genetic silencing of α-enolase in rat hearts and cultured cardiomyocytes attenuated Dox-induced apoptosis and mitochondrial dysfunction. In contrast, overexpression of wide-type or catalytically inactive α-enolase in cardiomyocytes mimicked the detrimental role of Dox in inducing apoptosis and ATP reduction. AMPK dephosphorylation was further demonstrated to be involved in the proapoptotic and ATP-depriving effects of α-enolase. Conclusion: Our findings provided the evidence that α-enolase has a catalytically independent role in inducing cardiomyocyte apoptosis and mitochondrial dysfunction, which could be at least partially contributed to the inhibition of AMPK phosphorylation. Highlights: Dox upregulated cardiac α-enolase expression. Genetic silencing of α-enolase attenuated Dox-induced cardiomyocyte injury. Overexpression of α-enolase resulted in cardiomyocyte injury. AMPK was involved in the proapoptotic and ATP-depriving effects of α-enolase.